1992
DOI: 10.1136/jech.46.3.222
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness study of the management of intractable urinary incontinence by urinary catheterisation or incontinence pads.

Abstract: Study objective-The aim was to compare the costs and effects of management of intractable urinary incontinence by urinary catheterisation or incontinence pads.Design-This was a prospective, randomised study comparing catheterisation with pads, supplemented by additional data collected from patients with chronic indwelling catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 14 publications
(2 reference statements)
1
20
0
Order By: Relevance
“…Cost data at the individual patient level were also included by Schnelle [1990] who compared the costs of prompted voiding to the costs of single pad and bed sheet changes. McMurdoe et al [1992] costed the nursing sta¡ time plus consumable costs of urinary catheterisation compared to continence pads. None of these studies reported detailed individual costs of care over multiple 24 hr periods in a consecutive series of patients, and the cost of faecal incontinence was not considered separately.…”
Section: Introductionmentioning
confidence: 99%
“…Cost data at the individual patient level were also included by Schnelle [1990] who compared the costs of prompted voiding to the costs of single pad and bed sheet changes. McMurdoe et al [1992] costed the nursing sta¡ time plus consumable costs of urinary catheterisation compared to continence pads. None of these studies reported detailed individual costs of care over multiple 24 hr periods in a consecutive series of patients, and the cost of faecal incontinence was not considered separately.…”
Section: Introductionmentioning
confidence: 99%
“…Incontinence pads may be used for bedridden patients, for patients who experience significant difficulty moving onto a toilet, or due to lack of adequate staffing needed to toilet residents with limited mobility. 11 While proper and improper use of incontinence pads has been documented in residential care, home care, and in nursing homes, [1][2][3][4] no studies have yet been conducted to assess the risk of using incontinence pads in patients admitted to acute-care facilities. The use of incontinence pads also affects caregivers, who may need to devote additional time for preventive skin management, pad application, and pad changes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…91,92 Nurses favored bed pads because they perceived the risk of urinary tract infection to be greater with catheters. 91 Another study compared indwelling internal and condom catheters.…”
Section: Type Of Study Outcomementioning
confidence: 98%
“…91,92 Nurses favored bed pads because they perceived the risk of urinary tract infection to be greater with catheters. 91 Another study compared indwelling internal and condom catheters. 97 In that study, patients found the urinary catheters to be less comfortable and more restricting, but nurses believed that they were easier to care for than penile sheaths.…”
Section: Type Of Study Outcomementioning
confidence: 98%
See 1 more Smart Citation